Assessing Florida Early Career Extension Faculty's Adoption of Design Principles to Communicate Messages - Peyton N. Beattie; Matt Benge; Ricky W Telg; Lisa K Lundy (Journal of Applied Communications, 2022)
Extension faculty are tasked with developing and communicating educational programs to local clientele, and communication skills are a considerable piece of the Extension faculty job. Thus, UF/IFAS Extension included a communication portion to the on-board training for newly hired Extension faculty to develop their design skills so they can more effectively communicate through their educational and marketing materials. We used Rogers’ (2003) innovation-decision process to assess Florida early career Extension faculty’s adoption of design principles after completion of the 2019 UF/IFAS Extension Faculty Development Academy. Thirty-two Extension faculty completed the spring and fall sessions of the Academy. A mixed methods approach was utilized to gather survey data at the immediate completion of the Academy and qualitative, telephone interview data four to five months after completing the Academy. The faculty retrospectively perceived they increased their knowledge about design principles. They had an overwhelmingly positive attitude about learning design principles to better their communication efforts, but they decided not to fully adopt design principles in their work as other information and elements of learning their job took precedent.
Keywords: Extension; design principles; training and development